Current and Future Trends of Construction Project Performance Models: A Review - Mtana, Method H.; Mwaluko, George S.; Matindana, Juma M. (Tanzania Journal of Engineering and Technology, 2025)
The construction industry (CI) has experienced outstanding growth and contributed to economic growth for many countries, with enormous foreign investments that require quality projects. High pressure to reduce the construction cost and time commonly put the industry at risk of lower quality and safety of the construction facilities. Like many other developing countries, Tanzania needs more stringent quality control measures in the construction sector to contribute positively to sustainable growth. This study thus reviews current and future trends in construction industry performance in Tanzania. The literature review on construction projects (CPs) performance is based on information on time overruns from contractors, clients, and consultants of the Tanzanian CIs. Initially, 300 literatures were reviewed and manually screened to about 50 literatures. Results showed that 56% of the 50 reviewed literatures indicate the need to reduce the time overruns in CPs. Further, it was noted that more responsibility in addressing time and cost overrun challenges in the CPs lies on clients, consultants, and contractors. Moreover, planning scheduling factors (PSF) is noted to be the most noteworthy category of factors that greatly influence project performance. In contrast, records and documentation factors (RDF) scored as the second most significant factor in performance in terms of cost overruns. The study, therefore, concludes that contractors, clients, and consultants should have an adequate cash flow plan, properly manage financial resources, advance site management through experts, and institute appropriate planning and scheduling. Thus, these research findings propose factors that lead to time overrun, thus portraying the establishment of robust systems to eliminate time overrun causes.